A Study on Risk Management in Corporate Business - Saradha Balaji; Lolakpuri Shreshta; K. Sujatha (PT Agung Media Publisher, 2024)
The complexity of today's corporate landscape underscores the importance of robust risk management strategies for organizational resilience and sustainability. This study investigates the methodologies and effectiveness of risk management practices in corporate settings, emphasizing key components that contribute to success. Using a mixed-methods approach, the study surveyed 100 corporate managers and conducted in-depth interviews with 20 senior risk management professionals. Findings indicate that companies with comprehensive risk management frameworks perform significantly better in mitigating risks compared to those with minimal strategies. Key elements identified include proactive risk assessment, continuous monitoring, and integration into corporate culture. Senior management involvement also correlates positively with effective risk management outcomes. Despite recognition of its importance, challenges such as resource constraints, inadequate training, and resistance to change hinder implementation. The study highlights the need for ongoing improvement in risk management practices through enhanced training and greater leadership engagement. It stresses the critical role of structured risk management in corporate sustainability and resilience, advocating for further research into innovative tools and strategies to meet evolving business challenges.